2002
DOI: 10.1001/jama.287.21.2815
|View full text |Cite
|
Sign up to set email alerts
|

Extrapolation of Correlation Between 2 Variables in 4 General Medical Journals

Abstract: A high proportion of the articles analyzed from all 4 weekly general medical journals involved extrapolation without indication. Researchers, reviewers, and editors should be aware of this problem and work to eliminate it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 45 publications
0
12
0
3
Order By: Relevance
“…While they found that the majority of subjects with heavy prenatal alcohol exposure performed worse than expected based on nonlinear regression estimates of WCST and IQ scores derived from a large comparison group, data from some heavily exposed subjects appear outside the range of IQ scores obtained in the comparison group. In regression, extrapolation outside of the range of scores used to derive the line can result in erroneous or unreliable conclusions (Cohen et al., 2003; Kuo, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While they found that the majority of subjects with heavy prenatal alcohol exposure performed worse than expected based on nonlinear regression estimates of WCST and IQ scores derived from a large comparison group, data from some heavily exposed subjects appear outside the range of IQ scores obtained in the comparison group. In regression, extrapolation outside of the range of scores used to derive the line can result in erroneous or unreliable conclusions (Cohen et al., 2003; Kuo, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, these results should be interpreted cautiously since the heavily exposed subjects with the lowest IQ scores do not appear to fall within the range of scores used to calculate the regression lines. Regression lines tend to be unreliable when based on few observations (i.e., at the extremes of a distribution) and extrapolation can lead to extraneous results (Cohen et al., 2003; Kuo, 2002). No studies using the CST exist with which to compare results to general intellectual functioning.…”
mentioning
confidence: 99%
“…Much of the problematic usage of regression analysis is not derived from flaws in the methodology itself, but from the lack of consideration given to the requisite assumptions for drawing valid inferences based on the method, for example, failure of the strict exogeneity assumption (Porter 1999), or the failure to consider the consequences of diagnostic problems such as influence points or extrapolation off support of the data (Kuo 2002). Failures on any of these dimensions can lead to inferences that are seriously flawed.…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, this dataset would have provided no support for the 'mixing vessel' hypothesis if all the data used to construct the phylogeny had also been used in the regression analysis. There is always a risk in drawing conclusions from extrapolation of a regression analysis (Kuo 2002). In the case of emerging infectious disease, this technique is especially suspect because extrapolation relies on the assumption of a constant rate of evolution over time.…”
Section: Retrospective Analyses Based On Phylogeneticsmentioning
confidence: 99%